Building the politics machine: tools for "resolving" the global land grab - Dwyer, M.B. (Wiley, 2013)
The recent proliferation of transnational land deals has put the long‐fraught relationship between international cooperation, national development and local dispossession back in the political spotlight. This article argues that transnational land access cannot be resolved as a political question without a better understanding of the material, legal and administrative geographies that accompany and enable it. Using evidence from Laos, the paper illustrates two tools for ‘resolving’ the global land grab geographically: first, a biographical or trajectory‐based approach that connects specific land grabs to larger development landscapes (e.g. of urban infrastructuring); and second, genealogies of property formalization that interrogate and deconstruct the legal geographies of land access, both on and off the map. The paper concludes by suggesting that these tools have purchase elsewhere as well.